Mesoniviruses are mosquito-specific viruses with extensive geographic distribution and host range - Vasilakis, Nikos (BioMed Central, 2014)
BACKGROUND: The family Mesoniviridae (order Nidovirales) comprises of a group of positive-sense, single-stranded RNA ([+]ssRNA) viruses isolated from mosquitoes. FINDINGS: Thirteen novel insect-specific virus isolates were obtained from mosquitoes collected in Indonesia, Thailand and the USA. By electron microscopy, the virions appeared as spherical particles with a diameter of ~50 nm. Their 20,129 nt to 20,777 nt genomes consist of positive-sense, single-stranded RNA with a poly-A tail. Four isolates from Houston, Texas, and one isolate from Java, Indonesia, were identified as variants of the species Alphamesonivirus-1 which also includes Nam Dinh virus (NDiV) from Vietnam and Cavally virus (CavV) from Côte d’Ivoire. The eight other isolates were identified as variants of three new mesoniviruses, based on genome organization and pairwise evolutionary distances: Karang Sari virus (KSaV) from Java, Bontag Baru virus (BBaV) from Java and Kalimantan, and Kamphaeng Phet virus (KPhV) from Thailand. In comparison with NDiV, the three new mesoniviruses each contained a long insertion (180 – 588 nt) of unknown function in the 5’ region of ORF1a, which accounted for much of the difference in genome size. The insertions contained various short imperfect repeats and may have arisen by recombination or sequence duplication. CONCLUSIONS: In summary, based on their genome organizations and phylogenetic relationships, thirteen new viruses were identified as members of the family Mesoniviridae, order Nidovirales. Species demarcation criteria employed previously for mesoniviruses would place five of these isolates in the same species as NDiV and CavV (Alphamesonivirus-1) and the other eight isolates would represent three new mesonivirus species (Alphamesonivirus-5, Alphamesonivirus-6 and Alphamesonivirus-7). The observed spatiotemporal distribution over widespread geographic regions and broad species host range in mosquitoes suggests that mesoniviruses may be common in mosquito populations worldwide.